"Psychosomatic consultation in the workplace" - a new model of care at the interface of company-supported mental health care and consultation-liaison psychosomatics: design of a mixed methods implementation study - Rothermund Eva; Kilian Reinhold; Hoelzer Michael; Mayer Dorothea; Mauss Daniel; Krueger Marc; Rieger Monika A; Guendel Harald (BMC, 2012)
Abstract Background Mental health issues are gaining in importance in society and the economic system. At the same time, the accessibility and stigmatisation of the mental health care system in Germany can obstruct help-seeking behavior and delay early psychotherapeutic interventions. Therefore, new models of care are being established at the interface of company-supported health promotion and conventional health insurance sponsored outpatient care for people developing mental illnesses. Two large industrial companies, in cooperation with two psychosomatic clinics, have recently established a model of "psychosomatic consultation in the workplace". This new model of care offers the opportunity for a first psychotherapeutic door to door consultation with occupational medicine within the industrial workplace. The main empirical goals of this study are: 1) Describing the differences between patients who use this new diagnostic and therapeutic offer within the industrial workplace vs. patients who visit a conventional regional outpatient clinic, especially in regard to symptom duration and severity, work ability, and demographic characteristics, and 2) A first evaluation of how patients may benefit more from this new model of care compared to those first seen by standard outpatient care. In the qualitative part of the study, occupational physicians, psychosomatic therapists, involved personnel and select employees of the involved companies will be asked to comment on their experiences with this new approach. Methods/Design The implementation study will take place in Ulm and in Stuttgart, with each site looking at one regional conventional psychosomatic outpatient clinic and one psychosomatic consultation offer within the workplace. 70 consecutive patients in each setting will be recruited (overall n = 280). For the cross-sectional study and pre-post comparison we will use established and validated survey instruments (PHQ, SF-12, WAI, MBI, IS) as well as standardized questions about health care use. For data analysis, we will use uni- and multivariate analytical methods. Qualitative data analysis (expert interviews) will be carried out using Mayring's content analysis method. Discussion The results of this study have the potential to provide evidence-based knowledge about an innovative model of psychotherapeutic outpatient care and to further promote tailored solutions for early psychotherapeutic interventions within the worksite. Trial Registration DRKS00003184